DISIPLIN KERJA, KOMITMEN ORGANISASI, MOTIVASI, DAN KINERJA KARYAWAN PT POS INDONESIA (PERSERO) CABANG ENDE - Menge, Theresia; Mea, Maria Helena Carolinda Dua; Sari, Santy Permata (ANALISIS, 2025)
This study seeks to examine the impact of work discipline, organizational commitment, and motivation on employee performance at PT Pos Indonesia (Persero) Ende Branch. This study primarily addresses the inconsistency in employee performance, which is believed to be affected by internal organizational issues. This research employed a quantitative methodology via a survey technique. Data were gathered via questionnaires administered to 33 employees as participants. The employed analytical method was multiple linear regression to evaluate the simultaneous and partial impacts of each independent variable on employee performance. The findings indicated that work discipline, organizational commitment, and motivation collectively exerted a substantial impact on employee performance. All three variables exhibited a favorable and significant impact on performance to some extent.